The effect of preventative exercises designed to reduce shoulder joint ligament injury on the volleyball spiking skill for Al Salam University College players - Al-Tamimi, Asst.L. Iman Kazem Hani (Sulaimani Journal for Humanities, 2025)
The importance of preventative exercises is paramount due to their effective impact on maintaining physical fitness and strengthening and improving the flexibility of body parts for all sports. The shoulder joint is one of the most mobile joints in the human body, due to the daily activities and exercise involved. Therefore, it is essential to emphasize the use of preventative exercises in aquatic environments to reduce the pressure on the joint. Through research and data collection, the researcher obtained positive results when using preventative exercises on the sample, demonstrating increased joint strength and flexibility, thus reducing the risk of injury.